Permanence, Extinction and Periodic Solution of a Non-autonomous Cooperative System with Stage Structure. Issue 1 (March 2020) - Halik, Azhar; Muhammadhaji, Ahmadjan; Mahemuti, Rouzimaimaiti
Abstract: This paper studies a class of non-autonomous two-species cooperative system with stage structure. Some sufficient conditions on the boundedness, permanence, extinction, periodic solution of the system are established by using the comparison method.